Google : How Google works - Schmidt, Eric, 1955 April 27-; Rosenberg, Jonathan, 1961-; Eagle, Alan (Crand Central Publishing, 2014)
"Jack Welch's Straight from the Gut was once the essential primer for managers, but today's leaders need a new playbook. In HOW GOOGLE WORKS, Eric Schmidt and Jonathan Rosenberg distill their decades of working in the high-tech industry into a practical and fun-to-read guide for those who want to succeed in an ever-changing business landscape. The book offers how-to advice on strategy, corporate culture, talent, decision-making, innovation, communication and dealing with disruption. The authors explain how the confluence of three seismic changes--the internet, mobile, and cloud computing--has shifted the balance of power between consumer and corporation. The companies that thrive will be the ones that create superior products and attract a new breed of multi-faceted employees whom the authors dub "smart creatives." The management maxims are illustrated with previously unreported anecdotes from Google's corporate history. "Back in 2010, Eric and I created an internal class for Google managers focusing on the lessons the management team learned the hard way," says Rosenberg. "The class slides all said 'Google confidential' until an employee suggested we uphold the spirit of openness and share them with the world. This book codifies the recipe for our secret sauce: how Google innovates and how Google empowers employees to succeed.""--